Preparation and biological assessment of some aromatic hydrazones derived from hydrazides of phenolic acids and aromatic aldehydes - Moussa, Ziad (Heliyon, 2020)
There has been substantial interest over the past many years in the design of novel chemical compounds containing the azomethine group (-NH-N=CH) and exhibiting various medicinal properties such as antibacterial, antiviral, antifungal, and anti-inflammatory activities. Herein, hydrazones were synthesized via the chemical reaction of substituted aromatic hydrazides with various aromatic aldehydes. The obtained products were confirmed using different physical and spectroscopic techniques, such as m.p., IR, (1)H-NMR and (13)C-NMR. The present study was designed to synthesize different aromatic hydrazones assembled by various combinations of aromatic hydrazides and aromatic benzaldehydes containing different substituents such as hydroxyl and polyhydroxyl groups as key structural features. Thus, incorporating such moieties and simultaneously creating highly-conjugated systems was expected to create novel species to mimic as much as possible natural phenolics, chalcones and stilbenes. Compounds of aromatic hydrazones synthesized in the present study were tested in vitro for their direct and indirect antioxidant activities using different methods such as DPPH, ABTS and FTC. The antioxidant activities of the new compounds ranged from very weak to very high activity. In addition, the inhibition of tyrosinase and cholinesterase by these compounds was tested. The new compounds containing two or three hydroxyl groups attached to aldehyde rings exhibited significantly greater inhibition effects on tyrosinase or cholinesterase activities in comparison to other compounds of the same series containing only one hydroxyl group.